Fundamental and advanced fetal imaging : ultrasound and mri - Kline-Fath, Beth M; Bulas, Dorothy I; Lee, Wesley (Wolters Kluwer Health, 2021)
The publication focuses on prenatal ultrasound and fetal magnetic resonance imaging in assessment of fetal disorders. Intended for professionals.
Keywords: vrozené vady; radiologie, nukleární medicína a zobrazovací metody; Congenital Abnormalities; vývoj plodu; Fetal Development; plod; ultrazvuk; nemoci plodu; embryologie a teratologie; Ultrasonography, Prenatal; Ultrasonics; Magnetic Resonance Imaging; Fetus; Fetal Diseases; magnetická rezonanční tomografie; ultrasonografie prenatální; perinatologie a neonatologie